KONSISTENSI SELISIH ANTARA NILAI LABA AKUNTANSI DAN KABA PAJAK DAN KUALITAS INFORMASI DARI LABA - Poespawijaya, Natalia (University of Surabaya, 2016)
This study aimed to see if the consistency of the difference in value accounting profit and tax profit (book-tax differences) affect the information content of earnings. Past research has often tried to link the relationship between tax information as supplementary information from the financial statements of commercial information when commercial financial report as containing a lot of manipulation of the results of this study ditermukan that there is no effect of the difference in value between accounting profit and income taxes on earnings informativeness. Additionally, ditermukan pulabahwa no influence between the level of aggressiveness of tax planning and management of the companys earnings informativeness of accounting profit nor taxable profits. These different results can occur because information about the tax is still very limited in Indonesia so that it becomes irrelevant information in decision-making and can not be fully captured by investors.